2004
DOI: 10.1097/00001756-200404290-00027
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of spatial attentional asymmetries with poor sustained attention

Abstract: The co-existence of deficits in sustained and spatial attention in patients with acquired damage to the right cerebral hemisphere has led to the proposition that sustained attention could be a marker for left spatial inattention, or neglect. We investigated the possibility that reductions in leftward spatial attentional asymmetries could arise from individual differences in the capacity for sustained attention even within healthy adult populations. We observed that healthy participants who performed poorly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 23 publications
2
32
2
Order By: Relevance
“…The results provide further evidence for the postulated influential role of the alertness network on the network of visuospatial attention (Bellgrove et al, 2004;Fimm et al, 2006;Manly et al, 2005;Robertson et al, 1998) in a 3D virtual reality setting. Thus, we were able to replicate previous findings of a link between low arousal and attentional asymmetries (Fimm et al, 2006).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The results provide further evidence for the postulated influential role of the alertness network on the network of visuospatial attention (Bellgrove et al, 2004;Fimm et al, 2006;Manly et al, 2005;Robertson et al, 1998) in a 3D virtual reality setting. Thus, we were able to replicate previous findings of a link between low arousal and attentional asymmetries (Fimm et al, 2006).…”
Section: Discussionsupporting
confidence: 55%
“…Thimm et al (2006) demonstrated how computerized alertness training can improve visuospatial performance of neglect patients and that this is linked to reactivation in right hemisphere brain areas (frontal cortex, anterior cingulate cortex, precuneus, and angular gyrus) associated with alerting and visuospatial attention. Bellgrove et al (2004) demonstrated how individual differences in alertness capacity can modulate pseudoneglect (the small leftward attentional bias in healthy subjects), whereas Callejas et al (2004) identified an accelerating influence of alerting on orienting. In a recent study (Fimm et al, 2006), we provoked attentional asymmetries in healthy subjects by short-term sleep deprivation (28 hr) leading to a substantial reduction of arousal associated with a significant slowing of responses to stimuli presented to the left visual hemifield as well as a facilitation of covert reorienting of attention toward the right visual hemifield.…”
Section: Introductionmentioning
confidence: 99%
“…The sustained attention task used in this investigation was a variant of the Sustained Attention to Response Test (SART) [7] that includes a dual-task element [25]. Previous work with this version of the SART has established its relationship to the original SART and its sensitivity to index transient lapses of attention [25].…”
Section: Sustained Attention Taskmentioning
confidence: 99%
“…Previous work with this version of the SART has established its relationship to the original SART and its sensitivity to index transient lapses of attention [25].…”
Section: Sustained Attention Taskmentioning
confidence: 99%
See 1 more Smart Citation